A retrograde object near Jupiter's orbit. (February 2018) - Connors, M.; Wiegert, P.
Abstract: Asteroid 2007 VW266 is among the rare objects with a heliocentric retrograde orbit, and its semimajor axis is within a Hill sphere radius of that of Jupiter. This raised the interesting possibility that it could be in co-orbital retrograde resonance with Jupiter, a second "counter-orbital" object in addition to recently discovered 2015 BZ509 . We find instead that the object is in 13/14 retrograde mean motion resonance (also referred to as 13/-14). The object is shown to have entered its present orbit about 1700 years ago, and it will leave it in about 8000 years, both through close approach to Jupiter. Entry and exit states both avoid 1:1 retrograde resonance, but the retrograde nature is preserved. The temporary stable state is due to an elliptic orbit with high inclination keeping nodal passages far from the associated planet. We discuss the motion of this unusual object based on modeling and theory, and its observational prospects. Highlights: A second object is now known in a retrograde resonance near Jupiter's orbit. The resonance is shown to be 13/-14 in mean motion, at high absolute inclination. A coarse determination of perihelion regression explains temporarily stability. Recent developments in theory should allow more precise theoretical discussion. Observational aspects are discussed, which may favor recovery of the object in the near term.